Variação genética para caracteres silviculturais e anatômicos da madeira em progênies de Myracrodruon urundeuva (Engler) Fr. Allem - Tung, Ellen Su Ching [UNESP]; Freitas, Miguel Luiz Menezes; Florsheim, Sandra Monteiro Borges; De Lima, Israel Luiz; Longui, Eduardo Luiz; Santos, Fernando Wergles; De Moraes, Mário Luiz Teixeira [UNESP]; Sebbenn, Alexandre Magno (My University, 2010)
The aims of this study were to evaluate the variation and to estimate genetic parameters for silvicultural anatomic wood traits for genetic breeding of a Myracrodruon urundeuva (Engler) Fr. Allem, population from Selvíria-MS. For this, from samples of a progeny test established in the Fazenda de Ensino, Pesquisa e Extensão da Faculdade de Engenharia de Ilha Solteira/UNESP, macroscopic anatomic wood traits of M. urundeuva (tangential diameter and vases frequency per mm2) and growth traits were measured (height, DBH and stem form). Genetic parameters were estimated in 28 open-pollinated progenies, in three replications and 10 plants per plot, using a REML/BLUP approach. Between the analysed traits, the DBH is the most indicated for selection for timber production, because it presented the highest values of coefficient of genetic variation, heritabilities and selective accuracy. Between the anatomic traits, the vessels frequency in the pith showed the highest values for genetic parameters. For pulp yield, based on the multi-effect index, the strategy of selecting the best trees for vessels frequency in the pith, independent of the progeny, permitted to obtain substantial gains by mass selection, without progeny test.
Genetic variation for silvicultural and anatomical traits of wood in progenies of Myracrodruon urundeuva (Engler) Fr. Allem
Keywords: Aroeira; Diameter and frequency of vessels; Genetic conservation; Progeny test; Tree breeding; Progeny tests; Genes; Forestry; Astronium; Diameter; Genetics; Progeny; Yield